Về thành phần hóa học và hoạt tính sinh học cây ngoại mộc tái (Allophylus livescens Gagnep.) thu hái tại vùng Vịnh Hạ Long - Tâm, Khiếu Thị; Thiện, Đào Đức; Hoàng Anh, Nguyễn Thị; Thủy, Trịnh Thị; Lộc, Trần Văn; Sung, Trần Văn (Vietnam Journal of Chemistry, 2016)
Allophylus livescens Gagnep, a flowering plant of Sapindaceae family. It is an endemic plant growing in limestone mountains of Halong bay. Until now, there have been no phytochemical and biological activity works about this species. This is the first report on the isolation and structural elucidation of five constituents from A. livescens’s leaves and twigs. These compounds named: 1,6,10,14-phytatetraene-3-ol, catechin, stigmasterol, b-sitosterol and b-sitosterol glucoside. The cytotoxic assay on five human cancer cell lines (KB, Hep G2, LU-1, MCF-7, SK) of compound 1,6,10,14-phytatetraene-3-ol showed negative result. Keywords. Allophylus livescens Gagnep, endemic, 1,6,10,14-phytatetraene-3-ol.